EFEKTIVITAS KEBIJAKAN PELAYANAN PEMBUATAN KARTU KELUARGA DAN KTP ELEKTRONIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA JAYAPURA - Masyita B (JURNAL KEBIJAKAN PUBLIK, 2020)
This article aims to knowing and analyzing the effectiveness of population document service policies in the Making of Family Cards and E-KTP in Jayapura City Population and Civil Registration Service, Knowing and analyzing factors that support and hinder the effectiveness of population document service policies in making Family Cards and E-KTPs at the Jayapura City Population and Civil Registration Service, and Knowing and analyzing efforts to improve the effectiveness of population document service policies in making Family Cards and E-KTPs at the Jayapura City Population and Civil Registration Service. This study uses a qualitative research method approach that seeks to construct reality and understand its meaning, so it is very concerned about processes, events and authenticity. The emphasis of qualitative research is intended to examine the condition of the subject, by finding and finding information through limited but in-depth case studies with a holistic description. The results of the study showed that the effectiveness of the Population Document Service Policy in the Making of Family Cards and E-KTPs at the Jayapura City Population and Civil Registration Service had been carried out in accordance with applicable procedures and regulations. The Jayapura City Population and Civil Registry Service pays attention to the five aspects mentioned above, namely tangible, reliability, responsiveness, assurance and empathy. Supporting Factors for the Effectiveness of Service Policies for Population Documents in Making Family Cards and E-KTPs at the Jayapura City Population and Civil Registration Service include: transparency of services provided and adequate infrastructure, while inhibiting factors consist of: apparatus resources possessed, community awareness in do services, facilities and infrastructure that exist and the distance between Districts and Sub-Districts to Jayapura City. Efforts to Overcome Problems of Service Effectiveness of Population Documents in Making Family Cards and E-KTPs at the Jayapura City Population and Civil Registration Service include: conducting programs, providing services that are not burdensome and difficult for the community, proposing procurement of service support facilities, and accelerating development street access to the capital city.